Peran Trade Creation pada Produk dari China Terhadap Impor pakaian di Indonesia - Irgi Saeful Rizky; Andika Alexandro; Adinda Faniyah Yusha (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
International trade plays a strategic role in driving economic growth, especially for developing countries like Indonesia. Through trade activities, countries can access products with more economical prices or superior quality while expanding the market for their local products. One important concept in international trade is trade creation, which is an increase in the volume of trade between countries as a result of the reduction or elimination of tariff and non-tariff barriers. This concept allows goods produced more efficiently in other countries to be imported to replace more expensive or less efficient domestic products (Baier & Bergstrand, 2020). As a developing country, Indonesia is also active in international trade and has significant trade relations with China, particularly in the textile and apparel sector, where China has become the largest trading partner in recent years.